Influence of Pre-Oxidation on Dual Atmosphere Effect on AISI 441 Interconnects for Solid Oxide Fuel Cell Applications. (30th May 2017) - Goebel, Claudia; Alnegren, Patrik; Faust, Robin Leonard; Svensson, Jan-Erik; Froitzheim, Jan
Abstract : In previous studies an extreme dual atmosphere effect on the air-facing side of AISI 441 at 600 °C was observed. However indications showed that pre-oxidation of the material might have a beneficial effect on the corrosion resistance in dual atmosphere. To examine this further we pre-oxidized AISI 441 samples for 0 min, 11 min, 45 min, 180 min and 280 min and subsequently exposed these at 600 °C for 500 h under dual atmosphere conditions. Photographs of the air-facing sides were taken throughout exposure to monitor the corrosion behavior. SEM analysis was performed on all samples after exposure.